Experimental and reliability studies on the behaviour of concrete columns reinforced internally with glass fibre reinforced polymer reinforcements - Deiveegan, A.; Kumaran, G. (Journal of Structural Engineering, 2024)
This study covers on the experimental and reliability studies on the behaviour of concrete columns reinforced with non- metallic reinforcements under axial and eccentric loadings. The experimental investigation consists of twenty four column specimens in each series with different parameters like shape of columns, reinforcement ratios, types of Glass Fibre Reinforced Polymer Reinforcements (GFRP) reinforcements, slenderness of the columns and grades of concrete. Based on this study, the strength expressions are derived using the equilibrium, strain compatibility, and stress-strain relationship for the constituent materials. For a known eccentricity, the expressions for axial thrust-moment interaction relations are developed for slender columns and the effect of secondary moments incorporated in the analytical study. Also Finite element modelling and analysis of GFRP reinforced concrete columns are performed to simulate the behaviour of the columns under various parametric conditions. A probabilistic framework is necessitated because of the presence of a large number of uncertainties pertaining to the theoretical models and the inherent randomness in the various design parameters. The full range of possible values of load eccentricity, from axial load to pure bending is investigated in the study. Finally, based on the reliability index, appropriate resistance factors are arrived at using the concepts of reliability based design.